Penggunaan Komputer sebagai Media Pembelajaran di perguruan tinggi - Aris Saefulloh (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Although computer has been used in into the educational world since along ago, it is not intensively used as media in learning process at university. It usually used as media in learning process only for computer lesson. If its functions in a larger as media in learning process of other lessons, it hopefully became an alternative way to improve the quality of learning at university..